Supramolecular Encapsulation of a Neurotransmitter Serotonin by Cucurbit[7]uril - Chandra, Falguni; Dutta, Tanoy; Koner, Apurba L. (Frontiers in Chemistry, 2020)
pH-dependent host-guest complexation of a monoamine neurotransmitter, Serotonin, with cucurbit[7]uril has been thoroughly investigated. The binding phenomena were explored using steady-state and time-resolved fluorescence spectroscopy at different pH values. At lower pH, i.e., protonated Serotonin, the binding affinity with cucurbit[7]uril was significantly higher compared to higher pH. Furthermore, detailed NMR titration experiments depicted the solution structure of the host-guest complex through the complexation induced chemical shift values. A competitive binding assay with cesium ions at pD 2.8 was subsequently performed for the further manifestation of the binding. Finally, the molecular docking studies provided well-documented proof of the 1:1 inclusion complex and the geometry of the complex. We believe that understanding from such studies can be important for pH-controlled delivery of serotonin for biological applications.